Kelayakan Usaha Budidaya Cacing Tanah Eisenia feotida di Era New Normal Covid-19 untuk Meningkatkan Pendapatan Masyarakat - Mashur Mashur; Hunaepi Hunaepi (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This study aims to determine the feasibility of developing Eisenia foetida earthworm cultivation with multilevel shelf technology as a new source of income to increase income for the community in the New Normal Era of Covid-19. The research was carried out at the Earthworm Teaching Farm in Mandalika Village, Mataram City, West Nusa Tenggara Province in January-June 2020. The components of cultivation technology applied were three-storey shelf technology, plastic tub nest box, earthworm stocking density of 25 grams/ nest box, using a mixed media of 50% horse feces, 50% rice straw, 50% goat feces mixed feed, and 50% rumen contents that have been fermented for three weeks. The results showed that, B/C >1.0; the IRR value is greater than the prevailing interest rate (>18-40%) and the NPV value is >0. The net income of cultivators during one production cycle (40 days) is Rp. 9,231,300. If a year is harvested 8 times, then the net income is Rp. 73,850,400 per year with three-storey shelf technology or a net income rate that has been assessed now with an interest rate of 18% per annum Rp. 62,585,112 in the first year and Rp. 53,038,176 in the second year. The conclusion is that the development of the Eisenia foetida earthworm cultivation business with multilevel shelf technology on a business scale of 100 m2 is feasible to be developed as a new business for the community, especially earthworm cultivators because it can increase people's income in the New Normal Era of Covid-19.